Doença periodontal em cães - Ando, Natasha Fujii [UNESP] (2011)
Periodontal disease affects the periodontum which are tissues that support and protect the tooth and are composed by the gingiva, alveolar bone, cementum and periodontal ligament. Lesions in the periodontum have as main etiologic agent the presence of plaque or biofilm, which is formed in 24 hours and, basically, it consists of microorganisms surrounded by some bacteria rich matrix products and salivary glycoproteins. Gingivitis is the first clinical manifestation of periodontal disease and it is reversible if the etiologic agent (plaque) is removed. However, if it is not treated or controlled, it will lead to an irreversible periodontitis, and even evolve into alveolar bone, tissue destruction and, eventually, tooth loss